2014
DOI: 10.1103/physreve.89.013014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sedimentation on the threshold for Soret-driven convection in colloidal suspensions

Abstract: The onset of Soret-driven convection in a horizontal layer of a colloidal suspension is investigated by considering a particulate medium model. We consider a dilute suspension of spherical solid particles being subjected to convection in a Rayleigh-Bénard geometry setup. The mathematical model takes into account the effects of thermophoresis, particle sedimentation, and Brownian diffusion. The equations governing the convective motion consist of the momentum equation which includes an extra body force term to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…As it was shown in [19], for particles in the nanosize range in the case of a negligibly small thermal expansion coefficient, when the thermally induced buoyancy was absent, threshold conditions for instability derived through the particulate medium model were consistent with ones obtained through the binary mixture model for Soret-driven convection with a large and positive separation ratio. Works [20,21] extended the study of Hadji [19] by considering the effect of thermal field and the dependence of viscosity and diffusion coefficient on concentration. The authors revealed that an increase in the fluid viscosity and decrease in the diffusion coefficient due to the presence of particles had an overall destabilizing effect on the onset of convection.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As it was shown in [19], for particles in the nanosize range in the case of a negligibly small thermal expansion coefficient, when the thermally induced buoyancy was absent, threshold conditions for instability derived through the particulate medium model were consistent with ones obtained through the binary mixture model for Soret-driven convection with a large and positive separation ratio. Works [20,21] extended the study of Hadji [19] by considering the effect of thermal field and the dependence of viscosity and diffusion coefficient on concentration. The authors revealed that an increase in the fluid viscosity and decrease in the diffusion coefficient due to the presence of particles had an overall destabilizing effect on the onset of convection.…”
Section: Introductionmentioning
confidence: 99%
“…The first concerns the Soret-driven convection of a suspension with particles in the nanosize range (binary mixture model) [15][16][17]. The second one involves both the particle size and particle volume fraction and deals with the sedimentation and thermo-migration of particles under an imposed temperature gradient in the gravity field (particulate medium model) [18][19][20][21]. A long wave-length asymptotic analysis was conducted to obtain a stability boundary for a mass-dominated regime of convection in a dilute suspension [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations